Surviving lockdown: The making of final project from final year AD117 student / Mohammad Firdaus Azman... [et al.] - Azman, Mohammad Firdaus; Yaacob, Mohd Nuri; Azuddin, Muhammad Asri; Halili, Nurakma; Shafie, Norhaslinda (UiTM Perak Press, 2022)
In general Coronavirus disease 2019 (COVID-19) is defined as illness caused by a novel coronavirus now called severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2; formerly called 2019-nCoV), which was first identified amid an outbreak of respiratory illness cases in Wuhan City, Hubei Province, China (Cennimo, 2022). The COVID-19 pandemic is a serious global health threat (National Center for Immunization and Respiratory Diseases (NCIRD), 2020) and this virus until now (2021) has not recovered. In Malaysia, all sectors are affected, including the education sector. Various measures have been taken to curb the spread of the virus among students and staff. One of them is to conduct online learning activities.